METHODOLOGICAL RECOMMENDATIONS FOR THE USING OF MODERN TOOLS IN LEARNING MATHIMATICS IN THE CONTEXT OF THE NEW UKRAINIAN SCHOOL - Простакова, Юлія; Єрмоленко, Віра (SWorldJournal, 2025)
The article discusses the using of modern tools in teaching mathematics in the context of the New Ukrainian School. It reveals the relevance of digital tools, such as graphic calculators, interactive platforms, online whiteboards, and simulators, to impr